2015
DOI: 10.1111/sms.12550
|View full text |Cite
|
Sign up to set email alerts
|

MR‐based in vivo follow‐up study of Achilles tendon volume and hydration state after ankle‐loading activity

Abstract: The purpose of this study was to evaluate temporal alterations of the Achilles tendon volume and hydration state after cross-country-running. Achilles tendons of six untrained participants were examined on a 3T MR-scanner before running, immediately afterwards, and in the following 24, 48, and 72 h. Using a 3D-UTE sequence, caudal (CA) and cranial (CR) mid-portion tendon areas were examined with off-resonance saturation ratios (OSR) and T2* relaxation times. Tendon volume was measured with a self-written Matla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…Grosse et al. (19) showed that T2* values are decreased by prior physical activity. In the present study, the patients were inactive during the initial scan (∼40 min) and for approximately 45 min between the scans; consequently, the increase in T2* could reflect a slightly higher free water content after a period of inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Grosse et al. (19) showed that T2* values are decreased by prior physical activity. In the present study, the patients were inactive during the initial scan (∼40 min) and for approximately 45 min between the scans; consequently, the increase in T2* could reflect a slightly higher free water content after a period of inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated conditioning of the free tendon, as observed in the current study is likely due to some combination of differences in tendon structure, composition, and loading between free AT and aponeurosis. Factors such as complex fascicle/fiber orientation (Szaro et al., ; Edama et al., ), fascicle/fiber sliding as a result of elastic behavior of interfascicular matrix (Slane & Thelen, ; Thorpe et al., ), high collagen fiber crimp angle (Magnusson et al., ) as well as fluid redistribution under load (Syha et al., ; Grosse et al., ) have been reported to contribute to the unique mechanical behavior of the free AT. The free tendon is also longitudinally tensioned by forces from all three triceps surae muscles, whereas the aponeurosis experiences transverse strain due to soleus muscle bulging (Iwanuma et al., ; Farris et al., ; Bojsen‐Møller & Magnusson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently highlighted the non‐uniform nature of AT mechanical properties between the free AT and aponeurosis, with the free AT demonstrating greater compliance compared to the aponeurosis during mechanical testing both before (Finni et al., ; Magnusson et al., ; Farris et al., ) and following exercise‐induced fatigue loading (Lichtwark et al., ; Obst et al., ). The free AT also experiences torsion of tendon fascicles (Szaro et al., ; Edama et al., ), and has a high fiber crimp angle (Magnusson et al., ), and substantial fluid content (Syha et al., ; Grosse et al., ). It is therefore possible that the number of conditioning contractions required to reach steady‐state longitudinal strain may differ between the free AT and whole AT.…”
mentioning
confidence: 99%
“…The proximal AT therefore does not appear to be vulnerable to strain-related injuries during repeated loading in MAT. Differences in tendon anatomical structure [fascicle/fibre orientation (Szaro et al, 2009), fluid content (Grosse et al, 2016) and crimp angle (Magnusson et al, 2002)], the magnitude and direction of the load exerted, and loading distribution pattern (Iwanuma et al, 2011;Farris et al, 2013;Reeves and Cooper, 2017) between proximal AT and free AT have been proposed as possible mechanisms underpinning the isolated creep behaviour of the free AT during repeated loading (Nuri et al, 2016).…”
Section: Contralateral Tendinopathymentioning
confidence: 99%